Pharmacology activity, toxicity, and clinical trials of Erythrina genus plants (Fabaceae): an evidence-based review - Susilawati, Elis; Levita, Jutti; Susilawati, Yasmiwar; Sumiwi, Sri Adi (Frontiers in Pharmacology, 2023)
The concept of using plants to alleviate diseases is always challenging. In West Java, Indonesia, a local plant, named dadap serep has been traditionally used to reduce blood glucose, fever, and edema, by pounding the leaves and applying them on the inflamed skin, or boiled and consumed as herbal tea. This plant belongs to the Erythrina genus, which covers approximately 120 species. The scope of this review (1943 to 2023) is related to the Global Development Goals, in particular Goal 3: Good Health and Wellbeing, by focusing on the pharmacology activity, toxicity, and clinical trials of Erythrina genus plants and their metabolites, e.g., pterocarpans, alkaloids, and flavonoids. Articles were searched on PubMed and ScienceDirect databases, using 'Erythrina' AND 'pharmacology activity' keywords, and only original articles written in English and open access were included. In vitro and in vivo studies reveal promising results, particularly for antibacterial and anticancer activities. The toxicity and clinical studies of Erythrina genus plants are limitedly reported. Considering that extensive caution should be taken when prescribing botanical drugs for patients parallelly taking a narrow therapeutic window drug, it is confirmed that no interactions of the Erythrina genus were recorded, indicating the safety of the studied plants. We, therefore, concluded that Erythrina genus plants are promising to be further explored for their effects in various signaling pathways as future plant-based drug candidates.